An Eye toward Equity: Redesigning Course Scheduling within Guided Pathways Reform Efforts. Issue 2 (1st February 2023) - Sublett, Cameron; Orenstein, Ari
ABSTRACT: While community colleges excel at expanding postsecondary enrollments, these institutions often struggle to help students succeed. A chorus of school leaders and policymakers increasingly agree that broad-based, comprehensive organizational change is needed to drastically improve community college student success and equity. The Guided Pathways reform model has been increasingly adopted in recent years by institutions looking to usher in such change. This paper explores an important but overlooked aspect of guided pathways reforms: course scheduling practices and how such practices can be redesigned to improve the experiences and outcomes of racially minoritized student groups.